Application of Krashen’s Input Hypothesis in a Listening Comprehension Blended Learning Classroom - Miran Abdulrahman Abdullah; Omar Fouad Ghafor (Zanco Journal of Human Sciences, 2026)
Listening remains central in EFL classrooms but is still under-studied, particularly for adolescents in low-resource settings. This study aimed to examine whether meaning-focused Comprehensible Input (CI) delivered in a blended format outperforms conventional accuracy-focused drills. Two intact eighth-grade classes (N = 44) at a K–8 school in Halabja, Kurdistan Region, Iraq, completed eight weeks of instruction. Listening was measured with parallel forms of the Cambridge A2 Key (KET) test, and baseline comparability was checked before analysis. An ANCOVA with pre-test as covariate showed a clear group effect favoring CI, F(1, 41) = 13.83, p < .001, partial η² = .252; adjusted means were 16.75 (SE = 0.30) for the experimental (CI) group and 15.16 (SE = 0.30) for the control group. A gain-score check pointed the same way (d = 1.05). Taken together, the findings suggest that abundant, level-matched input—supported by simple smartphone-based tools—can improve EFL listening for secondary learners. The study used class-level assignment (two clusters) and online engagement was not equated across groups; therefore, the results should be read with caution. To strengthen the evidence and aid classroom adoption, future work should use more classes with cluster randomization, include fidelity checks, and add follow-up testing to see whether gains last.